2020
DOI: 10.1111/jocn.15210
|View full text |Cite
|
Sign up to set email alerts
|

The impact of street clothes among caregivers on residents with dementia in special care units: The STRECLO study

Abstract: Aims and objectives:To examine the impact of caregivers' street clothes on people living in special care units (SCUs). We hypothesised that caregivers wearing street clothes would improve residents' relationships with other residents and caregivers and, as a consequence, would improve their quality of life.Background: Environmental factors have been recognised as important elements in the care of people with dementia. Among these factors, the importance of the caregivers' appearance and more particularly their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Interviews and observational studies were conducted in several countries, exploring family members and nursing home staffs' perceptions of care and social interactions with residents. These studies found that overall, a meaningful social community is associated with increased resident quality of life and sense of dignity as well as staff well‐being 65–80 . Focus groups conducted with nursing home staff revealed that staff were better able to provide care to residents and mitigate resident‐to‐resident aggression when they understood the trajectory of ADRD 73,75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews and observational studies were conducted in several countries, exploring family members and nursing home staffs' perceptions of care and social interactions with residents. These studies found that overall, a meaningful social community is associated with increased resident quality of life and sense of dignity as well as staff well‐being 65–80 . Focus groups conducted with nursing home staff revealed that staff were better able to provide care to residents and mitigate resident‐to‐resident aggression when they understood the trajectory of ADRD 73,75 …”
Section: Resultsmentioning
confidence: 99%
“…These studies found that overall, a meaningful social community is associated with increased resident quality of life and sense of dignity as well as staff well-being. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] Focus groups conducted with nursing home staff revealed that staff were better able to provide care to residents and mitigate resident-to-resident aggression when they understood the trajectory of ADRD. 73,75…”
Section: International Countriesmentioning
confidence: 99%
“…The relational dynamic between the patient and the professional is also impacted by the presence, or absence, of the white coat. The absence of uniforms would establish a relationship of equals and force professionals to humanise their care ( Bailly et al, 2020 ; Charras & Gzil, 2013 ; Richardson, 1999 ). The resulting authenticity and relational reciprocity could promote a person-centred care model, which is currently recommended in the geriatric care sector ( Kogan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive help that we tend to provide to older adults, which stems from our paternalistic attitudes ( Vale et al, 2020 ; Sánchez-Izquierdo et al, 2019 ), can be reinforced by wearing a uniform. Moreover, healthcare professionals who stop wearing their white coat for a few months (or even more), tend to discover that patients or residents become less demanding and more independent ( Sparrow, 1991 ; Bailly et al, 2020 ). Instead of passively complying, patients or residents become more active and engaged ( Chu et al, 2020 ).…”
Section: Effects Of the White Coat On The Professional (“Enclothed Co...mentioning
confidence: 99%
See 1 more Smart Citation